Tanaidacea (Crustacea) from Macaronesia III. The shallow-water Tanaidomorpha from the Cape Verde archipelago - Larsen, Kim; Nagaoka, Ryoko; Froufe, Elsa (Zootaxa, 2012)
Three new species of Tanaidacea are described from the Cape Verde archipelago in the Mid-Atlantic, collected during thesampling program of the Laboratory of Marine Community Ecology and Evolution (LMCEE) to Macaronesia and formerPortuguese colonies. The new species belong to the tanaidomorphan families Leptocheliidae (Leptochelia parasavignyi), Paratanaidae (Paratanais vicentetis), and Pseudotanaidae (Pseudotanais Akanthinotanais breviaquas).